Pengaruh Sales Promotion, Personal Selling, dan Direct Marketing terhadap Keputusan Pembelian Makanan dan Minuman di Padma Resort Legian: (Studi Kasus pada Restoran yang ada di Padma Resort Legian) - Dewi, Ni Putu Diana Monica; Wimba, I Gusti Ayu; Dewi, I.A. Sasmita (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
The purchase decision is the stage where consumers have evaluated the product and can form an intention to buy the most preferred product for personal consumption. The purpose of this study was to determine the effect of sales promotion, personal selling, and direct marketing on food and beverage purchasing decisions at Padma Resort Legian. This research was conducted at Padma Resort Legian. The number of samples taken was 90 consumers with the nonprobability sampling method, and with the proportional random sampling technique. Data collection was carried out through observation (survey), interviews, literature study, documentation, and questionnaires. Testing research instruments using validity and reliability tests. The data analysis technique used is multiple linear regression analysis, analysis of the coefficient of determination, t-test (partial), and F-test (simultaneous). From the results of data analysis, it was found that sales promotion had a positive and significant effect on purchasing decisions, personal selling had a positive and significant effect on purchasing decisions, and direct marketing had a positive and significant effect on purchasing decisions, while simultaneously it was found that sales promoters, personal selling, and direct marketing have a positive and significant effect on purchasing decisions.